Critical Thinking Based Interactive Learning Media for Basic Mechanical Engineering - Aam Amaningsih Jumhur; Ratu Amilia Avianti; Anya Tamara Akbar (Jurnal Pendidikan Teknologi dan Kejuruan, 2021)
Recent studies show limited research on the development of learning media that effectively addresses critical thinking, communication, collaboration, and creativity(4C) characteristics. However, there is an urge for nurturing the 4C characters of vocational high school graduates in the 21st Century, especially critical thinking. Hence, this study aims to develop and discover the feasibility, usability, and effectiveness of critical thinking-based interactive learning media for Basic Mechanical Engineering. This study used the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) development concept. The information design in developing the learning media was based on critical thinking aspects by Facione in ATC21S. The critical-thinking-based interactive learning media (CTBILM) were developed for mobile learning which can be used in IOS and Android. The alpha test showed promising results, especially from material experts. In addition to that, the User Acceptance Test (UAT) also shown a significant score making CTBILM quite feasible. We also argue that the significant change in student critical thinking from the statistical t-test on pretest and posttest are due to CTBILM.